2014
DOI: 10.3844/ajbbsp.2014.1.13
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMIZATION OF ALKALINE PROTEASE PRODUCTION BY <i>STREPTOMYCES AMBOFACIENS</i> IN FREE AND IMMOBILIZED FORM

Abstract: Optimization of alkaline protease production by Streptomyces ambofaciens NRRL 2420 in free and immobilized form was investigated using submerged fermentation technique. The optimum conditions for maximum alkaline protease production 342 unit mL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Indeed, simple substrates such as casein and gelatin have a low solubility and give low enzyme activity yields in liquid medium. Many microbial protease production studies in liquid media have confirmed our results (Joo and Chang, 2005;Laxman et al, 2005;Tari et al, 2006;Chi et al, 2007;Abidi et al, 2008;Hajji et al, 2008 ;Abdelwahed et al, 2014). In addition, Lazim et al (2009) showed that the addition of casein in the solid culture medium containing wheat bran did not increase the protease production by the Streptomyces sp.…”
Section: Selection Of the Significant Factors For Protease Productionsupporting
confidence: 83%
“…Indeed, simple substrates such as casein and gelatin have a low solubility and give low enzyme activity yields in liquid medium. Many microbial protease production studies in liquid media have confirmed our results (Joo and Chang, 2005;Laxman et al, 2005;Tari et al, 2006;Chi et al, 2007;Abidi et al, 2008;Hajji et al, 2008 ;Abdelwahed et al, 2014). In addition, Lazim et al (2009) showed that the addition of casein in the solid culture medium containing wheat bran did not increase the protease production by the Streptomyces sp.…”
Section: Selection Of the Significant Factors For Protease Productionsupporting
confidence: 83%
“…Various techniques of cell immobilization are also useful in the production of enzymes such as α-amylase, β-amylase, xylanase, glucoamylase, pullulanase or alkaline phosphatase [13,90,91]. Viable, but non-growing immobilized Escherichia coli cells in biocatalytic films developed by Lyngberg et al [53] produced β-galactosidase with higher specific activity compared to suspended cells.…”
Section: Metabolic Responses To Immobilizationmentioning
confidence: 99%
“…have been reported to produce high levels of alkaline protease in culture media with pH ranging between 7 and 8.5. [33,35] Thermal stability…”
Section: ãããmentioning
confidence: 99%